MENINGKATKAN KETERAMPILAN PROSES SAINS MELALUI PENDEKATAN INKUIRI - Rini Susanti (JIV-Jurnal Ilmiah Visi, 2013)
The purpose of this research is to improve the science process skills of the children aged 5-6 years through inquiry approach at TK Kasih Ibu, South Jakarta. The research conducted in November and December 2012 employed classroom action research within two cycles. Each cycle consisted of planning, acting, observing, and reflecting. The subjects of this research were 12 kindergarten children. The data were collected using test and non test. After the second cycle, the research concluded that the inquiry approach can improve the science basic skills of children aged 5-6 years old. The implication of this research is inquiry approach can be alternative way to improve science process skills of children aged 5-6 years old. The improvement of the science basic science can be demonstrated through observing, comparing, classifying, measuring and communication.